Decitabine Inhibits Gamma Delta T Cell Cytotoxicity by Promoting KIR2DL2/3 Expression - Niu, Chao; Li, Min; Zhu, Shan; Chen, Yongchong; Zhou, Lei; Xu, Dongsheng; Li, Wei; Cui, Jiuwei; Liu, Yongjun; Chen, Jingtao (Frontiers in Immunology, 2018)
Gamma delta (γδ) T cells, which possess potent cytotoxicity against a wide range of cancer cells, have become a potential avenue for adoptive immunotherapy. Decitabine (DAC) has been reported to enhance the immunogenicity of tumor cells, thereby reinstating endogenous immune recognition and tumor lysis. However, DAC has also been demonstrated to have direct effects on immune cells. In this study, we report that DAC inhibits γδ T cell proliferation. In addition, DAC increases the number of KIR2DL2/3-positive γδ T cells, which are less cytotoxic than the KIR2DL2/3-negative γδ T cells. We found that DAC upregulated KIR2DL2/3 expression in KIR2DL2/3-negative γδ T cells by inhibiting KIR2DL2/3 promoter methylation, which enhances the binding of KIR2DL2/3 promoter to SP-1 and activates KIR2DL2/3 gene expression. Our data demonstrated that DAC can inhibit the function of human γδ T cells at both cellular and molecular levels, which confirms and extrapolates the results of previous studies showing that DAC can negatively regulate the function of NK cells and αβ T cells of the immune system.